Isolasi Senyawa Tiofen dari Bunga Tahi Ayam (Tagetes spp) Sebagai Odoran Gas LPG - Rosita Dwityaningsih; Zhilal Shadiq; Mohammad Nurhilal; Ayu Pramita; Septian Hanjaya (P3M Politeknik Negeri Cilacap, 2026)
Liquefied Petroleum Gas (LPG) is a mixture of propane and butane gases. LPG is characterized by being colorless and odorless, requiring an additive to act as an indicator of a leak in the gas cylinder, allowing it to spread into the air. The additive currently used as an odorant in LPG is ethyl mercaptan, a volatile liquid with a strong, pungent odor characteristic and highly stable, making it difficult to decompose in the air. However, this compound has drawbacks because the resulting aroma is difficult to detect, thus tending to irritate breathing and reduce user comfort. Therefore, it is necessary to isolate compounds from more environmentally friendly natural materials to become alternative odorants in LPG to replace ethyl mercaptan. One natural material that can be a source of compounds with strong aroma characteristics is the Tagetes spp. plant, which contains thiophene in its roots and leaves, making it a natural source of strong-smelling compounds. The results of this study were that the largest yield was obtained from the root extract with petroleum ether solvent of 5.85%, a corrosion rate of 6.63 µg/cm2.hour, and an odor level of 42. The high yield directly correlates with elevated odor intensity without inducing excessive corrosion, demonstrating the potential of Tagetes spp. root extract as a superior and safe natural odorant candidate.